PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM-ACHIEVEMENT DIVISION) BERBASIS MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV MATA PELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Natalia Pasaribu, Dhoa; Rika Perdana, Dayu; Nuraini, Siti; Nurwahidin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the low learning outcomes in Pancasila Education among fourth-grade students at SDN 5 Metro Timur. The research aims to determine the effect of the STAD (Student Team Achievement Division) cooperative learning model supported by audio-visual media on students’ learning outcomes. This study used a quasi-experimental design with a population and sample of 51 students selected through a census sampling technique. Data were collected through tests and observation sheets. Hypothesis testing using simple linear regression showed that F_calculated > F_table (31.465 > 4.26) with a significance value of 0.000 < 0.05. These results indicate that the STAD cooperative learning model assisted by audio-visual media has a significant effect on students’ learning outcomes.